Fatigue reliability assessment of small sample excavator working devices based on Bootstrap method - Yuhong Shao; Pengmin Lu; Binhua Wang; Qingyi Xiang (Fracture and Structural Integrity)
To evaluate the fatigue reliability of the excavator working device, the fatigue tests of 2 sets of moving arm and bucket rod of medium-sized excavators with self-weight of 26000 kg were carried out. The virtual augmented sample method (VASM) combined with Bootstrap method was used to analyze the reliability of the excavator working device under extreme small samples, and the interval and point estimations of life parameters were obtained. Based on the lognormal distribution of the excavator working device, the reliability evaluation model of the excavator working device was esTablelished, and reliability indexes, such as reliability function, failure distribution function, inefficiency function, reliable life and so on, were obtained. And the results of fatigue safety life under different confidence and reliability were calculated. The evaluation results show that the average failure time of the excavator working device is 5885 hours under the confidence of 75%, which provides an important reference for the design, the safety inspection and maintenance decision of the excavator working device.